Effect of adding sodium lactate and sorbic acid on Escherichia coli producing cytotoxic Vero toxin in red and white meat (Journal of Hama University, 2026)
Effect of adding sodium lactate and sorbic acid on Escherichia coli producing cytotoxic Vero toxin in red and white meatAbstract The aim of this research was to study the effect of sodium lactate and sorbic acid on Escherichia coli, which produces cytotoxic toxin (Vero-like) in red and white meat. These bacteria are considered a major cause of some meat-borne diseases and contribute significantly to meat spoilage. The aim was to inhibit the growth of these bacteria to the permissible limit. Meat samples were immersed in a sodium lactate solution (2% sodium lactate, 4% sodium lactate) and a sorbic acid solution (1% sorbic acid, 0% sorbic acid) for 30 minutes. The effect of sodium lactate and sorbic acid at different concentrations on these meats was then studied. The results were evaluated after testing the number of bacteria in the meat. The results demonstrated the ability of sodium lactate to inhibit the growth of these bacteria. Samples treated with a 4% sodium lactate solution showed better inhibition in these meats, and the results demonstrated the ability of sorbic acid to inhibit the growth of these bacteria. Samples treated with a 2% sorbic acid solution showed better inhibition of these meats. This study concludes that adding 4% sodium lactate can reduce the number of E. coli bacteria that produce a cytotoxic toxin for Vero cells. Adding 2% sorbic acid can also reduce the number of these bacteria, and the results showed significant differences at P